Study on the development of ambidextry through football in high school students - Tatarcan Cătălin-Andrei; Grosu Bogdan-Marius (Editura Univeristatii "Stefan cel Mare" din Suceava, 2024)
This study explores the impact of using soccer tools in the development of ambidexterity in secondary school students. We applied some exercises specific to the football game to evaluate the effects on the development of ambidexterity in secondary school students. The study included 28 students, divided into intervention and control groups. The target group followed a soccer-specific training program for 12 weeks, which included specific skill development exercises. Assessments before and after the intervention included juggling tests (keeping the ball in the air) and hitting the ball. The results indicated significant improvements in the target group compared to the control group. These improvements emphasize the effectiveness of soccer-specific exercises in developing ambidexterity and general coordination in middle school students. The conclusions suggest that the integration of such exercises and their practice in physical education classes can bring significant benefits in the development of motor skills and in the sports performance of students.